1980
DOI: 10.1093/nar/8.17.3829
|View full text |Cite
|
Sign up to set email alerts
|

The 5′-cytosine in CCGG1is methylated in two eukaryotic DNAS and Msp I is sensitive to methylatlon at this site

Abstract: Novikoff rat hepatoma and bovine liver DNAs were digested with Msp I or Hpa II. Restriction fragments were end-labeled using [alpha-32P]-dCTP and the Klenow fragment of E. coli DNA polymerase I and then digested to 2'-deoxyribonucleoside-3'-monophosphates using micrococcal nuclease and spleen phosphodiesterase. Mononucleotides were separated by two-dimensional thin layer chromatography, localized by radioautography, and the [32P]-label quantitated by scintillation spectrometry. This method, based on known spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…This cytosine is partially methylated in higher plants. The results of this experiment are especially puzzling because it has been reported that this cytosine is methylated in a tissue-specific manner at Msp I sites (23), including those at the 5' ends of the human -A and yv genes (21 (26). Furthermore, it has been shown that on the average, active genes are about 50% undermethylated at all C-G residues (27).…”
Section: Methodsmentioning
confidence: 84%
“…This cytosine is partially methylated in higher plants. The results of this experiment are especially puzzling because it has been reported that this cytosine is methylated in a tissue-specific manner at Msp I sites (23), including those at the 5' ends of the human -A and yv genes (21 (26). Furthermore, it has been shown that on the average, active genes are about 50% undermethylated at all C-G residues (27).…”
Section: Methodsmentioning
confidence: 84%
“…The bands at 1.22 and 3.7 kb are probably explained by polymorphism at a second MspI site at the other end of the intron (Fig. 7), although the presence of mCpC in some of the sites may also be the explanation (68).…”
Section: Resultsmentioning
confidence: 97%
“…In eukaryotes the modified base 5-mC (C*) occurs predominantly in the sequence 5'-C*pG-3' (Dosko~il & ~orm, 1962;Grippo et al, 1968), but 5-mC has also been found in 5'-C*pC-3' (Salomon & Kaye, 1970;Sneider, 1980;Gruenbaum et al, 1981;Romanov & Vanyushin, 1981) and 5'-C*pT-3' sequences (Salomon & Kaye, 1970;Sneider, 1972). The degree of methylation of C in these sequences varies greatly depending on many parameters, such as species, type of gene and stage of development.…”
Section: On the Biochemistry Of Dna Methylationmentioning
confidence: 99%
“…Whenever the internal C-residue of the sequence is modified to 5'-CC*GG-3' by methylation, the endonuclease HpaII cannot cut, whereas MspI does cut at such sites. Conversely, methylation of the external C, 5'-C*CGG-3', renders MspI refractory, while the endonuclease HpaII remains fully active (Sneider, 1980). The availability of this isoschizomeric pair of restriction enzymes with a complementary refractoriness for methylation facilitates the elucidation of methylation patterns in specific genes.…”
Section: W Doerflermentioning
confidence: 99%